CatStronauts Vol. 1, Mission Moon - Brockington, Drew (Brockington, Drew. CatStronauts, 2017)
Alerted to a global energy crisis, the President consults with the World's Best Scientist, who suggests sending a special group of astronauts to turn the Moon into a solar power plant.